Effect of inorganic or organic selenium supplementation on nutrient intake and rumen microbial population and protein content in cattle and buffaloes - DUTT, CHANDER; CHHABRA, ARUN (The Indian Journal of Animal Sciences, 2011)
A study was conducted to monitor the effect of supplementation of inorganic or organic form of selenium (Se) on nutrient intake, rumen microbial mass and protein of microbial origin in cattle and buffaloes. For this, 3 rumen cannulated animals each of crossbred cattle (228.00±16.04 kg) and Murrah buffaloes (166.67±6.67 kg) were randomly distributed in 3 × 3 latin square (switch over) design. In treatment T1, the animals were given a basal diet (0.456 ppm Se) consisting of maize fodder and concentrate mixture (71: 29) to meet the nutrient requirements. The animals in other 2 groups were fed on similar diets as in T1 but were supplemented with 0.5 ppm Se either in the form of sodium selenite (inorganic Se; T2) or selenomethionine (organic Se; T3). The results showed no significant differences in nutrient intake, rumen bacterial and protozoal population and microbial protein among the treatments in both species. The mean DM, CP and TDN intakes were 2.29±0.07 and 2.31±0.07 kg/100 kg, 256.86±6.60 and 260.98±9.14 g/100 kg and 1.42±0.03 and 1.43±0.05 kg/100 body weight in cattle and buffaloes, respectively. Water intake was also comparable. The intake of nutrients was similar in cattle and buffaloes. However, in comparison to cattle, buffaloes showed significantly higher bacterial counts (10.74±0.45 vs. 9.51±0.67×109/ml; P